The experience of countries in Western Europe and South America for the implementation of gender education in the learning process - Дороніна, Т. С. (Pedagogy of Higher and Secondary Education, 2012)
Doronina T. The experience of countries in Western Europe and South America for the implementation of gender education in the learning process. The article is devoted to the results of research the practice of gender theory in the education system in Western Europe and North America, outlined possibilities of progressivw experience in solving problems in the comprehensive schools of Ukraine.